Assessing the Impact of Education Policies in Indonesia: Challenges, Achievement, and Future Direction - Ika Widiastuti (STAI Hubbulwathan Duri, 2025)
This study examines the impact of education policies in Indonesia over the past decade, focusing on challenges, achievements, and future directions for educational sustainability. The analysis is guided by the objectives of decentralization reforms and alignment with global standards such as the Sustainable Development Goals (SDGs). A systematic literature review was conducted, synthesizing findings from 25 peer-reviewed articles published between 2014 and 2024. Reputable journals were selected to ensure credibility and relevance. Key themes included policy frameworks, implementation outcomes, and regional disparities. The findings reveal significant achievements, such as increased school enrollment rates, reduced illiteracy, and greater inclusivity. However, challenges persist, including unequal resource distribution, inconsistent educational quality across regions, insufficient teacher training, and limited technological integration. Policies aimed at bridging equity gaps and fostering innovation remain underdeveloped. Despite substantial progress, systemic issues hinder the full realization of policy objectives. Effective implementation requires robust monitoring, stakeholder collaboration, and equity-focused initiatives. Best practices identified from the literature highlight the importance of adaptive strategies tailored to Indonesia's diverse educational landscape. The study emphasizes the need for enhanced policy design and execution to address existing challenges and ensure a resilient, inclusive education system. Strategic recommendations include strengthening teacher capacity, leveraging technology, and fostering equitable resource distribution to sustain long-term progress.